Surveillance of Salmonella Serovars in the Food Chain in Poland: A Five-Year Review (2016–2020) - Ewelina Skrzypiec; Magdalena Skarżyńska; Magdalena Zając; Renata Kwit; Anna Lalak; Aleksandra Śmiałowska-Węglińska; Emilia Mikos-Wojewoda; Paulina Pasim; Weronika Koza; Dominika Wojdat; Inga Bona; Dominika Pastuszka; et al. (Pathogens)
(1) Background: Understanding the distribution of Salmonella serovars in food, animals, and their environments is crucial for identifying infection sources and monitoring pathogen prevalence in the food chain. This study analysed Salmonella serovars in Poland from 2016 to 2020, focusing on their epidemiological significance. (2) Methods: Isolation of Salmonella was carried out following PN-EN ISO 6579 standards, and serotyping was performed using the White–Kauffmann–Le Minor scheme. A total of 7104 isolates were collected from food-producing animals, their environments, food of animal origin, feedingstuffs, and fertilisers. (3) Results: A total of 175 serovars were identified, with S. Enteritidis (n = 2905; 40.9%), S. Infantis (n = 1167; 16.4%), and S. Typhimurium (n = 360; 5.1%) being the most prevalent. Species-specific patterns were observed: S. Enteritidis dominated in chickens, ducks, and cattle; S. Kentucky in turkeys; S. Typhimurium in geese; and monophasic S. Typhimurium in pigs. S. Enteritidis and S. Infantis were most frequent in food of animal origin, especially broiler meat. In feedingstuffs, S. Agona was predominant, while fertilisers mostly contained S. Derby and S. Infantis. (4) Conclusions: The study highlights the source-dependent variety of Salmonella serovars and the importance of serotyping in tracing infection routes and preventing the spread of pathogens. Identifying the most common serovars supports the development of targeted preventive measures, including improved biosecurity, hygiene, and management practices to enhance food safety.